Waqf development in minority Muslim country: Singapore's experience / Mas Nooraini Mohiddin - Mohiddin, Mas Nooraini (Center for Islamic Philantrophy & Social Finance (CIPSF), 2019)
Waqf is one of the important mechanisme in Islamic economic structure in developing countries besides zakat. The institutional role of Waqf is to reduce government burden in developing and fulfil social needs especially for Muslim society. In the majority of Muslim countries nowadays, where they have strict Shariah laws, charities such as zakat are managed by government bodies. While in non-Muslim countries such practise are managed by voluntary agencies. The methodology for this study is secondary data approach by using data analysis from the related journals, articles, and papers. This paper will discuss the role of Waqf institution in minority Muslim states in order to meet socio-economic development particularly for Muslim society. In addition, to explore to what extent Waqf institution could achieve the objective which is to minimise the poverty and improve quality life based on experince that have been through by minority Muslim in Singapore. Moreover, to identify the obstacles or challenges that the minorty Muslim face in order to improve Waqf instituition among majority non-Muslim. This paper will end up with the suggestion that may contribute for Waqf development in such countries.